SOFTWARE ENGINEERING ETHICS IN A DIGITAL WORLD. - Rashid, Awais; Weckert, John; Lucas, Richard (Computer (00189162), 2009)
The article presents three cases to illustrate that the digital world phenomenon which improves accessibility of services and communal communication could also raise several ethical issues relating to privacy, monitoring and data protection and could also have the potential to cause harm. It discusses a legislation in Great Britain that pose three key challenges for software engineers designing systems for the digital world. The notion of ethics-aware software engineering is also advocated in the article, where ethical considerations are taken into account across the software development cycle.